The Effectiveness of Innovative Learning on Mathematical Problem-Solving Ability: Quasi-Experimental - Syariful Akbar; M. Imamuddin; Fathur Rahmi; Isnaniah Isnaniah (Universitas Tanjungpura, 2022)
Quasi-experimental research or quasi-experimental research is an innovation from true experimenters, including difficult research in the fields of education and social. Although this research is difficult to do, many researchers are also interested in using a quasi-experimental design in conducting research, especially in the field of mathematics. The high interest of researchers in this study is due to the fact that quasi-experimental research is most suitable to be applied in research in the field of mathematics education which is the subject of instructional research by educators and students. Quasi-experiments are used to make it easier to control due to non-functioning due to the control group as an external variable that also has an effect. The study conducted in this study used a literature review, broadly speaking, research data collection was based on observations of related research journal articles that had been carried out by other researchers before. Quasi-experimental studies as a research vehicle that aims to examine the application of quantitative research in testing students' problem-solving abilities. Researchers need more accurate methods to be applied, theoretical studies and analysis results can be concluded that quasi-experimental research can be used as an alternative to problem solving in problem-based mathematics learning. Based on the analysis of the researcher's interest, it can be seen that in fact the researcher uses a test instrument to see the effect of solving students' mathematical problems by applying the random sampling technique. Keywords: Quasi Experiment, Mathematical Problem Solving, Quantitative